Analisis Bibliometrik dengan VOSViewer: Studi Artificial Intelegence dalam Pendidikan - Iriyani, Sri Astuti; Hadi, Heri Sopian; Marlina, Marlina; Patty, Elyakim Nova Supriyedi; Irhas, Irhas (Universitas Nusantara PGRI Kediri, 2023)
The aim of this study was to explore trends in artificial intelligence research in education over the past 20 years. The method used to explore research trends is literature review through bibliometric analysis. The results of bibliometric analysis identify the core research or authors, as well as their relationships, by covering all related publications or specific fields. Publications related to artificial intelligence in education from 2003-2023 are taken from international journals indexed by Google Scholar. Research trends of artificial intelligence in education are visualized using the Vosviewer program. The results showed that the trend of artificial intelligence research in education is vulnerable in the last 20 years, namely artificial intelligence, future trends, educational programs, databases, students and technology.